1994
DOI: 10.1016/0002-9610(94)90109-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic splenectomy

Abstract: A technique for laparoscopic splenectomy is described. The patient is placed in the right semidecubitus position and pneumoperitoneum is prepared. The splenic artery and vein are exposed near the hilum, using a laparoscopic ultrasonic dissector. The larger vessels are doubly ligated, and the spleen is resected and maneuvered into a nylon surgical sack; the sack is removed through a 2-cm incision along the midaxillary line. This procedure has been used for four patients requiring splenectomy for benign disease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…However, when these patients also have significant hypersplenism, they are generally considered to be inoperable cases. On the other hand, we have also advocated the usefulness of a laparoscopic splenectomy [4,5]. Recently, we performed a laparoscopic splenectomy in a patient with secondary hypersplenism due to liver cirrhosis.…”
mentioning
confidence: 99%
“…However, when these patients also have significant hypersplenism, they are generally considered to be inoperable cases. On the other hand, we have also advocated the usefulness of a laparoscopic splenectomy [4,5]. Recently, we performed a laparoscopic splenectomy in a patient with secondary hypersplenism due to liver cirrhosis.…”
mentioning
confidence: 99%
“…These limitations have kept current data regarding laparoscopic splenectomy essentially anecdotal. [1][2][3][4] However, the potential advantages associated with the development of a minimally invasive form of splenectomy are considerable. Many patients with hematologic disorders such as immune thrombocytopenic purpura (ITP), thrombotic thrombocytopenic purpura, autoimmune hemolytic anemia, hereditary spherocytosis, and others can be cured or their condition can be improved by splenectomy.5 Avoidance of a major upper abdominal incision decreases postoperative pain and minimizes impairment of pulmonary function, thereby decreasing narcotic use and minimizing pulmonary complications, duration of ileus, and length of postoperative stay.…”
mentioning
confidence: 99%
“…To date, the indications for splenectomy in patients with chronic HCV have been for endoscopic treatment-resistant esophagogastric varices or HCC requiring other invasive therapies such as hepatectomy [10]. Although Kercher et al [12] reported that Lap-Sp allowed for the administration of IFN therapy in 12 cases of HCV cirrhosis, their study was limited by the small number of subjects and the relatively short follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Since splenectomy using laparoscopic devices was first reported in 1992, the indications for applying this technique have expanded [10][11][12]. Laparoscopic splenectomy (Lap-Sp) as treatment against hypersplenism with splenomegaly alone is not contraindicated for cirrhotic patients [11,12], but to date, evidence is lacking that Lap-Sp is effective for subsequent IFN therapy.…”
mentioning
confidence: 99%